PERSEPSI DAN MINAT SISWA SLBN WIRADESA PEKALONGAN MELANJUTKAN PENDIDIKAN DI PTKIN - Prayogi, Arditya; Katni Katni; Sigit Dwi Laksana; Delima; Yenti Apriyani (LPPM STAI Muhammadiyah Probolinggo, 2023)
Access to higher education for people with disabilities remains difficult for various reasons, including the requirement of